Large eddy simulations of flow field and heat transfer under partially confined slot jet impingement on a vibrating constant heat flux surface - Natarajan, T.; Jewkes, J.; Narayanaswamy, Ramesh; Chung, Y.; Lucey, A. (2014)
The paper describes the effect of oscillation of an impingement surface under a partially confined slot jet. Both the flow characteristics and the heat transfer characteristics are explored and presented. The numerical conditions were as follows: Reynolds number Re = 1000-2000, dimensionless distance between the nozzle and the impingement surface h/B = 4.0, surface oscillation frequency, f = 0-100 Hz and the amplitude a = 1.0 mm. The experimental data of Ichimiya and Yoshida [5] are taken as a baseline case and the present numerical results are compared with the experimental studies. The results compare well with the experimental work. The present numerical work serves as the basis for a wider study intended to optimise the thermofluidic characteristics of jets impinging upon oscillating surfaces.